2001
DOI: 10.1111/j.1574-6968.2001.tb09462.x
|View full text |Cite
|
Sign up to set email alerts
|

Leavening ability of baker's yeast exposed to hyperosmotic media

Abstract: To develop a simple and rapid method for enhancing the leavening ability of baker's yeast, we examined the fermentation ability of baker's yeast exposed to hyperosmotic media. When baker's yeast cells were incubated at 25 degrees C for 1 h in a hyperosmotic medium containing 0.5% yeast extract, 0.5% peptone and 20% sucrose, the cells showed a higher fermentation ability in the subsequent fermentation test than those untreated. The increased ratios were from 40 to 60% depending on the strains used. Glucose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…SSF of washed pretreated spruce slurry resulted in overall ethanol yields between 68.1 and 77.2%; the lowest ethanol yield being obtained in SSF of the substrate with highest initial concentration of fermentable sugars (see Figure 4). Hyperosmotic stress due to high sugar concentrations results in the accumulation of intracellular glycerol in yeast cells [19,28], which could explain the slight decrease in ethanol yield at the highest glucose concentrations. The differences in the ethanol yields from SSF of washed steam-pretreated spruce slurry with different initial concentrations of fermentable sugars are not sufficient to explain the difference in ethanol yields observed in batch SSF of whole steam-pretreated spruce slurry with and without prehydrolysis (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SSF of washed pretreated spruce slurry resulted in overall ethanol yields between 68.1 and 77.2%; the lowest ethanol yield being obtained in SSF of the substrate with highest initial concentration of fermentable sugars (see Figure 4). Hyperosmotic stress due to high sugar concentrations results in the accumulation of intracellular glycerol in yeast cells [19,28], which could explain the slight decrease in ethanol yield at the highest glucose concentrations. The differences in the ethanol yields from SSF of washed steam-pretreated spruce slurry with different initial concentrations of fermentable sugars are not sufficient to explain the difference in ethanol yields observed in batch SSF of whole steam-pretreated spruce slurry with and without prehydrolysis (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, high sugar concentrations can lead to high osmotic pressure in the fermentation medium, which is known to stress the yeast. The incubation of yeast in a medium containing high concentrations of different fermentable sugars has been shown to increase the fermentation ability of the yeast [19]. Thus, high initial concentrations of fermentable sugar as a result of prehydrolysis prior to SSF may influence the fermentation step in the process in various ways.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae cells incubated in 0.2 m glycerol are reported to have high leavening ability in dough containing a high concentration of sucrose (sweet dough). A hyperosmotic medium containing 0.5% yeast extract, 0.5% peptone, and 20% sucrose was developed to increase the fermentation ability of S. cerevisiae (Hirasawa & Yokoigawa, 2001). These authors found a high correlation between intracellular glycerol accumulation and the fermentation ability of the tested yeast.…”
Section: Resultsmentioning
confidence: 99%
“…The fermentation ability of the yeast cells in LSMLD medium was determined using the method described by Hirasawa and Yokoigawa (2001). An optimal amount of cell mass (0.36 ± 0.005 g dry weight) of yeast was inoculated into 50 ml LSMLD medium in a 150-ml conical flask at 30 °C without shaking.…”
Section: Methodsmentioning
confidence: 99%